2016
DOI: 10.7150/jbji.14342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Preserving and Radical Surgical Treatment in 32 Cases of Calcaneal Osteomyelitis

Abstract: Introduction. Radical procedures like calcanectomy and amputation performed for calcaneal osteomyelitis are regarded as effective in eradication of infection even though potentially functionally disabling. Bone sparing procedures offer better functional result at the expense of potentially worse infection control. The aim of the study has been to assess the influence of the surgical radicalism as much as the extent of bone infection on the final outcome in the surgical therapy of chronic calcaneal osteomyeliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 29 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…Of these, eight patients (25%) were treated with a drilling operation combined with insertion of collagen-gentamicin sponges, nine (28%) with debridement with or without fasciocutaneous flap, and 15 (47%) with a partial calcanectomy. Infection control and wound healing was achieved in 75% (n=6/8), 78% (n=7/9), and 73% (n=11/15), respectively 14. Patients treated with bone preservation showed lower infection control rates as well as lower patient satisfaction.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Of these, eight patients (25%) were treated with a drilling operation combined with insertion of collagen-gentamicin sponges, nine (28%) with debridement with or without fasciocutaneous flap, and 15 (47%) with a partial calcanectomy. Infection control and wound healing was achieved in 75% (n=6/8), 78% (n=7/9), and 73% (n=11/15), respectively 14. Patients treated with bone preservation showed lower infection control rates as well as lower patient satisfaction.…”
Section: Resultsmentioning
confidence: 96%
“…Nine studies described treatment in a single stage 9,10,13,14,16,18,21,23,24. Only 2 papers describe 2 stage procedures 11,20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes might be associated with absolute infection eradication as well as preservation of calcaneus integrity. In a recent study, Babiak et al (2016) compared the efficacy between bone-preserving strategies (debridement or drilling and collagen-gentamicin sponge) and radical surgical protocols (partial or total calcanec- ogous bone graft surgery, whereas in our study we only performed 1-stage surgery, facilitated by CS being totally biodegradable and not requiring a second surgery. It should be noted that, in this study, we included only non-diabetic foot patients, which may be the primary reason for our much lower amputation rate compared with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 10 were managed with wound dressing and 1 underwent a secondary debridement surgery to remove the residual CS; all of these patients recovered well. In addition, 1 patient died of a cause unrelated to amputation following limb-saving surgery in CO patients ranged from 4% to 20% (Baumhauer et al 1998, Schade 2012, Van Riet et al 2012, Walsh and Yates 2013, Babiak et al 2016. Even a recent study (Waibel et al 2019) showed that 50% of the CO patients had to undergo secondary below-knee amputation even if they had already received total calcanectomy.…”
Section: Infection Eradication Rate and Adverse Eventsmentioning
confidence: 99%